The impact of genetic variations in sofosbuvir metabolizing enzymes and innate immunity mediators on treatment outcome in HCV-infected patients. (January 2022) - Ibrahim, Marwa K.; AbdElrahman, Mohamed; Bader El Din, Noha G.; Tawfik, Salwa; Abd-Elsalam, Sherief; Omran, Dalia; Barakat, Amal Z.; Farouk, Sally; Elbatae, Hassan; El Awady, Mostafa K.
Abstract: Hepatitis C virus (HCV) is the leading cause of liver diseases worldwide. At present, combinations of different classes of direct-acting antiviral agents (DAAs) are used as treatment options for HCV, in which sofosbuvir (SOF) is the common DAA among different therapeutic regimes. In Egypt, SOF plus daclatasvir (DCV) is the widely used anti-HCV treatment protocol. Herein, we aimed to assess the association between 3 single-nucleotide polymorphisms (SNPs) at the genes coding for 2 SOF metabolizing enzymes: histidine triad nucleotide-binding protein 1 ( HINT1 ) rs4696/rs7728773 and nucleoside diphosphate kinase 1 ( NME1 ) rs3760468, together with the most potent anti-HCV innate molecule, i.e., interferon lambda 3 ( IFNL3 ) rs12979860 and the response to SOF/DCV in Egyptian patients chronically infected with genotype 4 (GT4). SNPs were genotyped using real-time PCR in DNA from patients who achieved sustained virological response (SVR) at 12 weeks post-SOF/DCV treatment (i.e., responders; n = 188), patients who failed to achieve SVR12 (i.e., non-responders; n = 109), and healthy controls (n = 62). Our results demonstrated that patients bearing HINT1 rs7728773 CT/TT (odds ratio 2.119, 95% CI 1.263–3.559, p = 0.005) and IFNL3 rs12979860 CC (odds ratio 3.995, 95% CI 2.126–7.740, p = 0.0001) were more likely to achieve SVR12. However, neither HINT1 rs4696 nor NME1 rs3760468 seems to contribute to the responsiveness to SOF/DCV. Binary regression analysis defined 5 predictor factors independently associated with SVR12: age, bilirubin, hemoglobin, early stages of fibrosis, and combined HINT1 rs7728773 and IFNL3 rs12979860 favorable and mixed genotypes (odds ratio 3.134, 95% CI 1.518–6.47, p = 0.002), and that was confirmed by the combined ROC curve for the 5 predictor factors (AUC = 0.91, 95% CI 0.869–0.95, P = 0.0001). In conclusion, these data suggest that the two SNPs have the potential in predicting the response rate to SOF/DCV treatment in patients infected with HCV GT4. This study is the first to investigate the pharmacogenetics of SOF metabolizing enzyme and introduce HINT1 rs7728773 as a novel SNP that predicts the treatment efficacy. Highlights: Egypt is the leading country for hepatitis C infection. Considerable numbers of patients in an overpopulated country like Egypt still do not achieve sustained virological response. Drug metabolism enzymes shape the treatment outcome in several diseases. Here, the response to Sofosbuvir-based treatment is attributed to single nucleotide polymorphism in one of Sofosbuvir metabolizing enzyme.